On the communicative achievements of foreign-language learners - Szczodrowski, Marian (Glottodidactica, 2018)
The structures of a foreign language, presented by a teacher-sender, are received by a learner as specific signals that are subject to phonetic-phonological and graphic-graphemic decoding. They are accordingly transferred to the foreign-language center, in which semanticgrammatical decoding is performed. Individual structures acquired in this fashion constitute constructive elements of the storage mechanism for learning language in the form of constant structure-matrices. In the process of the receptive-productive dynamization of the language’s structures, the learner simultaneously masters their effectiveness and potential, which make it possible to apply the codified information to current situations. Autonomous forms of learning a foreign language lead to an increase in the reserves of vocabulary and to its more effective application. Independent manipulation of a foreign language in emergent situations means that the learner develops the ability to use it in contacts with communicative partners.